Hope. IN Reflections from Scholars and Practitioners [column] dealing with wicked problems of government - Ocampo, Romeo B. (2018)
This essay explores the possibility of hope in dealing with difficult problems and failures of government through critical analysis and reforms of public planning and policy decisionmaking. It examines the assessments made by different authors of the failures of scientific planning and of the social sciences in informing planning and policy, and their
proposals for improving the concepts and methods for social, historical, and policy research. The first section introduces the basic ideas about wicked problems thought inherent in government and life and about hope as a realistic view of goals that are difficult but not impossible to reach. The succeeding sections deal with: (a) alternative modes of planning and decision-making; (b) accounts of the persistence and failings of grandiose schemes of “high-modernist” statecraft, and prescriptions to make planning more responsive to the complexity of unplanned development; (c) efforts to explain the failures of social science as due to its mistaken emulation of the hard sciences, and to re-orient it also toward prudential or practical wisdom; (d) long histories of why the West came to dominate the world, the choices made by some societies that led to their demise or success in overcoming crises, and ideas about how to improve history as a science; (e) unconventional innovations advocated in economic development planning and information systems design; and (f) my own concept of a middlerange bridge between competing reform proposals, as suggested by the notions of policy versus basic research and framework for understanding institutional diversity at sub-system or local levels of governance. Given the foregoing premises, we can hope to deal effectively with wicked problems of government.
Keywords: Essays; Hope; Public administration -- Philosophical aspects